2009
DOI: 10.2166/wh.2009.171
|View full text |Cite
|
Sign up to set email alerts
|

Reducing the impact of summer cattle grazing on water quality in the Sierra Nevada Mountains of California: a proposal

Abstract: The Sierra Nevada Mountain range serves as an important source of drinking water for the State of California. However, summer cattle grazing on federal lands affects the overall water quality yield from this essential watershed as cattle manure is washed into the lakes and streams or directly deposited into these bodies of water. This organic pollution introduces harmful microorganisms and also provides nutrients such as nitrogen and phosphorus which increase algae growth causing eutrophication of otherwise na… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 42 publications
0
12
0
1
Order By: Relevance
“…the United States and Australia), is indeed focused on limiting livestock grazing at lower altitudes or prohibiting it in mountain areas, to preserve water resources (e.g. drinking water quality standard) and high-altitude habitats (Derlet et al, 2010). This debate may even become a conflict in some protected areas such as the Victoria Alpine National Park (Australia), where the decision to permit cattle grazing produced a clash between cattlemen's interests and conservation measures (Fraser and Chisholm, 2000).…”
Section: > Transhumance and Water Quality: A Traditional Hazardmentioning
confidence: 99%
See 3 more Smart Citations
“…the United States and Australia), is indeed focused on limiting livestock grazing at lower altitudes or prohibiting it in mountain areas, to preserve water resources (e.g. drinking water quality standard) and high-altitude habitats (Derlet et al, 2010). This debate may even become a conflict in some protected areas such as the Victoria Alpine National Park (Australia), where the decision to permit cattle grazing produced a clash between cattlemen's interests and conservation measures (Fraser and Chisholm, 2000).…”
Section: > Transhumance and Water Quality: A Traditional Hazardmentioning
confidence: 99%
“…Under moderate grazing pressure, transhumance can improve the biodiversity of alpine vegetation and favor plant and animal species related to the open areas (Laiolo et al, 2004). Mountain aquatic ecosystems are particularly sensitive to livestock presence in their watersheds, due to the small buffering capacity of the alpine vegetation and soils (Derlet et al, 2010). As a result, slight environmental pollution may have a significant impact on aquatic ecosystems since the biogeochemical processes (e.g.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Swartz et al (2003) found a positive relationship between the amount of residential land use and drinking water nitrate concentration. Derlet et al (2010) proposed changes to the cattle grazing system in the Sierra Nevada Mountains as a means to further protect drinking water drawn from the area. Mehaffey et al (2005) showed that small decreases in urban and agricultural land in the drinking water watersheds for New York City led to detectable improvements in water quality.…”
Section: Discussionmentioning
confidence: 99%